Expansion of the mycobacterial “PUPylome” - Watrous, Jeramie (2009)
Selective degradation of cellular proteins offers an important mechanism to coordinate cellular processes including cell differentiation, defense, metabolic control, signal transduction and proliferation. While much is known about eukaryotic ubiquitination, we know little about the recently discovered ubiquitin-like protein in prokaryotes (PUP). Through expression of His(7) tagged PUP and exploitation of the characteristic +243 Da mass shift attributed to trypsinized PUPylated peptides, a global pull-down of protein targets for PUPylation in Mycobacterium smegmatis revealed 103 candidate PUPylation targets and 52 confirmed targets. Similar to eukaryotic ubiquitination, further analysis of these targets revealed neither primary sequence nor secondary structure homology at the point of attachment. Pathways containing PUPylated proteins include many central to rapid cell growth, such as glycolysis, gluconeogenesis, amino acid and mycolic acid metabolism and biosynthesis, as well as translation. Seventeen of the 29 nitrosylated protein targets previously identified in Mycobacterium tuberculosis were also identified as PUPylation candidates indicating a connection between PUP-mediated remodeling of critical metabolic pathways and the mycobacterial response to exogenous stress.